THR for Online Motorbike Taxis : Right or Policy? - Safina Rahmaniar Wanaputri (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Tunjangan Hari Raya is a non-basic wage that is expressly regulated in the Labor Law as one of the rights that must be received by workers. With the development of technology, the emergence of online application-based transportation then raises a new legal issue regarding the rights of online motorcycle taxi drivers as working partners with online-based transportation providers to receive Hari Raya allowances. So it is necessary to analyze the working relationship between online ojek drivers and online-based transportation provider companies to determine whether online ojek drivers are entitled to holiday allowances. This study will formulate two problems: how is the legal basis for the provision of holiday allowance as a worker's right within the framework of labor law in Indonesia, and how is the legal position of online ojek drivers in employment relations according to the Labor Law.